Sub-frontal niches of plankton communities driven by transport and trophic interactions at ocean fronts - I. Mangolte; M. Lévy; C. Haëck; M. D. Ohman (Biogeosciences, 2023)
Observations and theory have suggested that ocean fronts are ecological hotspots, associated with higher diversity and biomass across many trophic levels. The hypothesis that these hotspots are driven by frontal nutrient injections is seemingly supported by the frequent observation of opportunistic diatoms at fronts, but the behavior of the rest of the plankton community is largely unknown. Here we investigate the organization of planktonic communities across fronts by analyzing eight high-resolution transects in the California Current Ecosystem containing extensive data for 24 groups of bacteria, phytoplankton, and zooplankton. We find that a distinct frontal plankton community characterized by enhanced biomass of not only diatoms and copepods but many other groups of plankton such as chaetognaths, rhizarians, and appendicularians emerges over most fronts. Importantly, we find spatial variability at a finer scale (typically 1–5 km) than the width of the front itself (typically 10–30 km) with peaks of different plankton taxa at different locations across the width of a front. Our results suggest that multiple processes, including horizontal stirring and biotic interactions, are responsible for creating this fine-scale patchiness.